خريطة بحثية لأبحاث التربية العلمية في كليات التربية - محمد أسامة عبد العزيز, عامر (جامعة الوادي University of Eloued, 2018)
هدفت الدراسة الكشف عن واقع بحوث التربية العلمية في رسائل الماجستير التي تم انجازها في جامعتي الإسلامية والأزهر بغزة من عام (2010 م-2015م) وتقديم تصور لخريطة بحثية مستقبلية ولتحقيق هدف الدراسة تم استخدام المنهج الوصفي المسحي من خلال بطاقة تحليل المحتوى وحصر كافة رسائل الماجستير في التربية العلمية وبلغ عددها (48) رسالة . وأسفرت نتائج الدراسة أن توجهات التربية العلمية في جامعات غزة كانت في مجال (تعلم وتعليم العلوم ) بنسبة ( 39.6% ) ويليه مجال (التقويم في تعليم العلوم ) بنسبة( 22.9%) وحظي مجال (طرائق واستراتيجيات التدريس) بنسبة ( 22.2%)، وحظي المنهج شبه التجريبي لحل مشكلة الدراسة بنسبه (29.8% ) ولم تستخدم الدراسات المناهج البحثية الأخرى مثل المنهج النوعي والمختلط وتبين أن أكثر أدوات الدراسة استخداما وهو الاختبار بنسبة (57%) وتليه الاستبانة بنسبة (22.8%) ولم تتناول أي رسالة أساليب المنهج النوعي مثل المقابلة المعمقة وكذلك أشارت النتائج إلى أن أكثر الفئات استهدافا هي فئة (طلاب المرحلة الأساسية العليا ) بنسبة (37.3%) وأوصت الدراسة بالاهتمام بمجالات رئيسة مثل تقنيات التعلم ودمجها في عملية تعليم العلوم مع الاهتمام بالمنحى البيني والتكامل مع المناهج الأخرى واستخدام تصاميم تجريبية قوية وتوجه نحو البحوث الكيفية بأساليبها المختلفة . The study aimed at exploring the reality of researches of the scientific education in Master theses that have been done at the Islamic University and Al-Azahr University in Gaza between 2010 and 2015. It also aims to present a vision for a future research map. To achieve the aims of the study, a descriptive survey approach was employed using a content analysis form ,In addition , a total of (48) theses, which comprise all master's theses in science education were collected. The results of the study show that orientations of the scientific education in Gaza universities were in the field of learning and teaching of sciences (39.6%) followed by the field of assessment of teaching sciences (22.9%). The field of methods and strategies of teaching has the percentage of (22.2%) and the semi-experimental curriculum to solve the study problem has the percentage of (29.08%).The researches have not used other research methods such as qualitative method and a mixed method. It has been shown that the most used study tools were the test with a percentage of (57%) followed by questionnaire with a percentage of (22.8%). None of the researches has used any qualitative methods such as deep interview. The results of the study showed that the most target groups were the students of high primary period (37.3%). The study recommended focusing on essential fields such as techniques of teaching and integrating them into the process of teaching sciences and the focus on Curve chart and Integration with other methods and using strong experimental designs and directing towards qualitative researches with their various methods
بجامعات غزة من عام 2010 م-2015م
مقال
Keywords: خريطة بحثية؛ توجهات بحثية ؛أولويات البحث; Researching map; researching orientations; Research priority